Lessons with the Mystics: Refreshing Our Vision in Mid/Late Career - Gina Briefs-Elgin (Journal of the Assembly for Expanded Perspectives on Learning, 2008)
This paper explores surprising and restorative responses to mid/late career burnout from the perspective of four of the world's great Eastern mystical traditions: Hinduism, Sufism, Zen, and Kabbalah.